Passaging impact of H9N2 avian influenza virus in hamsters on its pathogenicity and genetic variability - Shaib, Houssam A.; Cochet, Nelly; Ribeiro, Thierry; Abdel Nour, Afif M; Nemer, Georges; Azhar, Esam; Iyer, Archana; Kumosani, Taha; Harakeh, Steve; Barbour, Elie K (The Journal of Infection in Developing Countries, 2014)
Introduction: Avian influenza viruses of the H9N2 subtype have been reported to cause human infections. This study demonstrates the impact of nasal viral passaging of avian H9N2 in hamsters on its cross species-pathogenic adaptability and variability of amino acid sequences of the hemagglutinin (HA) and neuraminidase (NA) stalk. Methodology: Three intranasal passagings of avian H9N2 in hamsters P1, P2, and P3 were accomplished. Morbidity signs and lesions were observed three days post viral inoculation. The HA test was used for presumptive detection of H9N2 virus in the trachea and lungs of the hamsters challenged with the differently passaged viruses. Different primers were used for PCR amplification of the HA1 and NA stalk regions of the differently passaged H9N2 viruses, followed by sequence alignment. Results: The morbidity signs indicated low pathogenicity of the differently passaged H9N2 viruses in hamsters. The frequency of gross and microscopic lesions in the tracheas and lungs were insignificantly different among hamsters challenged with the differently passaged H9N2 viruses (p > 0.05). There was 100% similarity in the amino acid sequence of the HA gene of most passaged viruses. The amino acid sequence of the neuraminidase in the third passaged H9N2 virus recovered from lungs showed a R46P mutation that might have a role in the pathogenic adaptability of P3 viruses in hamsters’ lungs. Conclusions: The apparent adaptation of avian H9N2 virus to mammalian cells is in agreement with the World Health Organization’s alertness for a possible public health threat by this adaptable virus.